The differences in intentions and reasons among the opponents of the caliphate of Ali ibn Abi Talib (RA) and the beginning of the intellectual division between (35-40 AH, 655-660 AD) (Journal of Human Sciences, 2026)
This research aims to trace and study the differences and contradictions among the opponents of the caliphate of Ali ibn Abi Talib (AR) during the period between 35-40 AH (655-660 CE). In addition to addressing the intellectual divisions and their impact on the state of the Islamic nation, it also examines the role played by Jewish elements, hypocrites, and those who had infiltrated Islam in creating problems and chaos by spreading unfamiliar and strange ideas that are far removed from Islamic principles. The researcher adopted a descriptive-analytical approach, appropriate to the nature of the subject, by analyzing the historical events that occurred during that period. The study reached several conclusions, the most important of which was that all the events, problems, and divisions that occurred during that period were the result of conspiracies and intrigues alien to Islamic principles.